SISTEM INFORMASI REKAPITULASI DATA OPERASIONAL BERBASIS WEBSITE PADA PT WAHANA ERA SEJAHTERA - Heni Listianingrum; Valiza Niswa Audina; Sarah Aprilia; Daning Nur Sulistyowati (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
In recent years, advances in information technology (IT) have contributed significantly to improving business processes and operational efficiency. However, the adoption and utilization of IT remain suboptimal in some organizations, including PT Wahana Era Sejahtera. The company's operational data management is still carried out conventionally through external reports in the form of PDF and Microsoft Excel files, which causes the risk of duplication, data loss, and difficulties in the information retrieval process. In addition, this condition hinders the monitoring of the company's performance and increases the risk of errors in checking employee data and work tools. This research focuses on the development of a web-based operational data management system for PT Wahana Era Sejahtera to improve the efficiency of recording, storing, retrieving, and monitoring operational data. The system was developed using the Prototype model within the Software Development Life Cycle (SDLC) framework. Evaluation through User Acceptance Testing (UAT) resulted in a score of 82.32%, indicating a high level of user acceptance. The findings demonstrate that the proposed system can support operational activities by reducing the risk of data duplication and data loss, facilitate information management and retrieval, and support the process of monitoring company performance and decision-making more quickly, precisely, and accurately.